Between National Borders and Legal Boundaries: Jurisdictional Limitations in Reaching Online Gambling Providers Abroad - Jaya Suastika, I Made; Novy Purwanto, I Wayan (Westscience Press, 2025)
The phenomenon of online gambling in Indonesia is increasingly worrying, marked by the increasing number of players and the involvement of Indonesian citizens as service providers from abroad. This situation presents challenges for law enforcement, particularly when perpetrators are located in countries that do not have legal cooperation with Indonesia. The ITE Law stipulates extraterritorial jurisdiction, which normatively authorizes action against perpetrators outside the country's territory. This study aims to analyze the regulation of extraterritorial jurisdiction in law enforcement against transnational online gambling perpetrators and proposes strengthening relevant legal instruments to increase the effectiveness of enforcement. This study uses a normative legal method with a statutory and conceptual approach. The results indicate that the regulation of extraterritorial jurisdiction in the ITE Law can serve as a legal basis for action against transnational online gambling perpetrators, but its implementation requires the support of stronger international cooperation instruments. Optimizing extradition treaties and mutual legal assistance in criminal matters is key to overcoming legal and technical obstacles. Furthermore, harmonization of legal interpretations between countries is necessary for effective law enforcement.